Raw Lacquer Extract from Toxicodendron vernicifluum in Combination with ONC201 Enhances the Inhibitory Effects on Colorectal Cancer Cell Activity - Zhezhu Jin; Yongjun Jin (Turkish Journal of Gastroenterology, 2023)
Background: The purpose of the present research was to explore the therapeutic impact of raw lacquer extract from Toxicodendron vernicifluum on colorectal cancer cells and to investigate the outcome of raw lacquer extract and ONC201 co-treatment on the activity of colorectal cancer cells. Methods: The cells of HCT116 were treated with raw lacquer extract, ONC201, or co-treatment. Subsequently, MTT, trypan blue staining, colony formation, annexin V/propidium iodide staining, wound healing, and transwell assays were performed to assess the effects of raw lacquer extract, ONC201 and the synthesis effect of co-treatment on cell activity, survival, proliferation, apoptosis, migration, and invasion in HCT116 cells. Western blotting and immunostaining assay were also performed to detect the expressions of tumor necrosis factor-related apoptosis-inducing ligand, death receptor-5, cleaved caspase-8, p-mTOR/mTOR, and p-S6K/S6K in cells. Results: The results showed that ONC201 and raw lacquer extract had effective anti-cancer effects on HCT116 cells. ONC201 and raw lacquer extract treatment on colorectal cancer cells inhibited cell viability and growth, as well as induced cell apoptosis and cell death of HCT116. The migration and invasion of HCT116 cells were also inhibited. Significantly, raw lacquer extract and ONC201 cotreatment further enhanced the anti-colorectal cancer cell activity in HCT116 cells. Western blotting and immunostaining assay showed that raw lacquer extract in combination with ONC201 induced tumor necrosis factor-related apoptosis-inducing ligand/death receptor-5 expression activation, inhibited the expression of cleaved caspase-8/procaspase-8, and reduced the expression of p-mTOR/mTOR and p-S6K/S6K. Conclusion: These results indicated that raw lacquer extract in combination with ONC201 enhanced the inhibitory effects on colorectal cancer cell activity. Cite this article as: Jin Z, Jin Y. Raw lacquer extract from toxicodendron vernicifluum in combination with ONC201 enhances the inhibitory effects on colorectal cancer cell activity. Turk J Gastroenterol. 2023;34(3):211-220.